Union of the Comoros : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This paper examines Comoros' weak domestic revenue and volatile windfall revenues. Weak revenue mobilization and the reliance on volatile one-off windfall gains remains a significant development challenge for Comoros. Weak revenue mobilization not only makes it more difficult for Comoros to finance its significant development needs, but also increases the budget's reliance on uncertain and volatile one-off revenue streams. Sustainably improving revenue mobilization based on realistic and attainable budgetary targets, is key for financing Comoros' medium to long-term development goals without endangering debt sustainability. Broadening the tax base and thereby increasing the tax ratio to develop more predictable budgetary financing sources will aid execution of Comoros' ambitious investment program that underpins the country's development strategy.